Development of interactive e-modules to improve students’ scientific literacy abilities: A literature review - Herlina, Elin; Abidin, Zaenal (Jurnal Mangifera Edu, 2024)
This research aims to investigate the development of the interactive e- Module in the context of improving students' scientific literacy skills. The approach employed in this research involved a systematic literature review, detailing the latest developments from 2019 to 2023 in the use of interactive e-Modules to enhance scientific literacy among students in Indonesia and abroad. The Meta-synthesis techniques were applied in this research. The samples utilized were sourced from 2019-2023 and were retrieved from international journals Google Scholar, Scopus, and Eric with the keyword "Interactive e-module and Scientific literacy”. A total of 233 journal articles were obtained and after being reviewed 209 articles were eliminated because they did not include international articles relevant to this research. Consequently, only 24 articles were used in this research. This type of research used Systematic Literature Review (SLR). The research findings indicate that the E-Module is based on Discovery Learning, STEM (Science, Technology, Engineering, and Mathematics), PBL (Problem-Based Learning), PjBL (Project-Based Learning), IBL (Inquiry-Based Learning), SETS (Science, Environment, Technology, Society), SSI (Socio Scientific Issues), and Flipped classroom can improve students' Scientific Literacy. The type of technology used in making E-Modules included Macromedia Flash, Virtual Laboratory, Flip PDF Professional, PhET Applications, and Articulate Storyline. The implications of this literature review are anticipated to provide direction for the development of educational policies, curriculum design, and further research to increase scientific literacy in the digital era.